1996
DOI: 10.1016/s0092-8674(00)81301-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Requirements for α4 Integrins during Fetal and Adult Hematopoiesis

Abstract: Mice chimeric for the expression of alpha4 integrins were used to dissect the roles of these receptors in development and traffic of lymphoid and myeloid cells. During fetal life, T cell development is alpha4 independent, but after birth further production of T cells becomes alpha4 dependent. Precursors for both T and B cells require alpha4 integrins for normal development within the bone marrow. In contrast, monocytes and natural killer cells can develop normally without alpha4 integrins. Thus, there are lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
226
0
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 320 publications
(236 citation statements)
references
References 65 publications
8
226
0
2
Order By: Relevance
“…In contrast, although there are T lymphocytes in the blood of ␣ 4 -null/RAG-2 chimeric mice (Fig. 1A), a severe defect occurs in T cell differentiation within the thymus in the absence of ␣ 4 integrins as previously described for chimeras on other backgrounds (17). In fact, histological analysis of the thymus in ␣ 5 and ␣ V chimeric mice shows cortical and medullary areas similar to those in controls, whereas in ␣ 4 chimeric mice the thymus appears atrophic a few weeks after birth (Fig.…”
Section: Differential Roles For ␣ 5 ␣ V and ␣ 4 Integrins During supporting
confidence: 67%
See 1 more Smart Citation
“…In contrast, although there are T lymphocytes in the blood of ␣ 4 -null/RAG-2 chimeric mice (Fig. 1A), a severe defect occurs in T cell differentiation within the thymus in the absence of ␣ 4 integrins as previously described for chimeras on other backgrounds (17). In fact, histological analysis of the thymus in ␣ 5 and ␣ V chimeric mice shows cortical and medullary areas similar to those in controls, whereas in ␣ 4 chimeric mice the thymus appears atrophic a few weeks after birth (Fig.…”
Section: Differential Roles For ␣ 5 ␣ V and ␣ 4 Integrins During supporting
confidence: 67%
“…Chimeric mice were generated by injection of ␣ 5 -, ␣ V -, or ␣ 4 -null or wildtype ES cells into blastocysts from C57BL6 or RAG-2 deficient mice as previously described (17). (For ␣ 5 -and ␣ 4 -null ES cells see Refs.…”
Section: Micementioning
confidence: 99%
“…␣ 4 ␤ 7 is a receptor for the mucosal addressin cell adhesion molecule (MAdCAM-1) (11), and is thereby involved in selective lymphocyte trafficking to mucosal lymphoid tissues (12). ␣ 4 ␤ 1 binds to endothelial cells via the vascular cell adhesion molecule, VCAM-1, and is mainly mediating lymphocyte migration into sites of inflammation (13) but not to PLN (14). L-Selectin has been identified as a lymphocyte homing receptor mediating binding to and entry into PLN (15).…”
Section: Introductionmentioning
confidence: 99%
“…The integrin ␣4␤1 has been studied extensively with respect to its role in inflammation and hematopoiesis (Lobb and Hemler, 1994;Arroyo et al, 1996), and more recently, it has been shown to function in neurons (Vogelezang et al, 2001;Wingerd et al, 2002). The ␣4␤1 integrin binds multiple ligands, including vascular cell adhesion molecule-1 (VCAM-1; Osborn et al, 1989), fibronectin's connecting sequence-1 (CS-1; Guan and Hynes, 1990), thrombospondin-1 (Yabkowitz et al, 1993), other ␣4 integrins (Altevogt et al, 1995), the propolypeptide of von Willebrand factor (Isobe et al, 1997), ICAM-4 (Spring et al, 2001), transglutaminase C (Isobe et al, 1999), and osteopontin (Bayless et al, 1998).…”
Section: Introductionmentioning
confidence: 99%